Friday

April 18, 2014

April 18, 2014

Posted by **dain** on Thursday, December 6, 2012 at 7:42pm.

- math -
**Steve**, Thursday, December 6, 2012 at 10:40pm(-u^-5v^2)^-1*u^3v

= (-u^5 v^-2)(u^3 v)

= -u^-2 v^-1

= -1/(u^2 v)

**Related Questions**

algebra - ((5v)/(v^3-5v^2+6v))-((4)/(v-2))-((3V)/(3-V))

math - 3vt+v(5v-7t 5v^2 - 7vt + 3vt combine the last two terms.. 5v^2-10vt ...

physics - Which of the following is forward biased? (i canna draw so plz manage ...

geometry - If m<FGK= 5v-2 and m<KGH=3v+8 find x

math - collect like terms 10u+5v-6u-7v -5v -5v=-2 -10u -10u =-16 answer=-18 is ...

physics - for an object sliding down an uneven incline, which of the following ...

math - Solve each equation: 11/3v+2 minus 3/4= 5 over 3v+2

math-volume - I'm confused with how to solve this problem, so help would be ...

algebra 1 - find the product v^2+v-12/5v+10*-v-2/v^2+5v+4

algbra - find the product v^2+v-12/5v+10*-v-2/v^2+5v+4